The impact of trade protectionism on global trade ("Journal "U". Economy. Management. Finance.", 2024)
The work reveals the peculiarities of the influence of trade protectionism on the processes of world trade.  The concept of protectionism is considered from the point of view of tools for managing trade and economic relations. This publication reflects the possibilities of purposeful organization of trade processes in the global space. The author studies the theoretical and practical significance of protectionism in the global economy, its impact on ensuring national interests in various countries. Protectionism is studied as a way to protect state development in the context of the globalization of the world economy.
Keywords: protectionism; world trade; trade relations; economic development; international trade; foreign economy; competitiveness; world economy; management